2011 IEEE International Conference on Communications (ICC) 2011
DOI: 10.1109/icc.2011.5962443
|View full text |Cite
|
Sign up to set email alerts
|

Flexible On-Line Construction of IRA Codes for Packet Erasure Correction with Application to Aeronautical Communications

Abstract: Abstract-In many applications erasure correcting codes are used to recover packet losses at high protocol stack layers. The objects (e.g. files) to be transmitted often have variable sizes, resulting in a variable number of packet to be encoded by the packet-level encoder. In this paper, algorithms for the (online) flexible design of parity-check matrices for irregular-repeataccumulate codes are investigated. The proposed algorithms allow designing in fast manner parity-check matrices that are suitable for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The adoption of a multicarrier technology provides the system with high spectral efficiency, increased robustness against multipath distortions, and a remarkable flexibility in assigning system resources. It was recently shown that further physical layer (PHY) advancements can be achieved by introducing packet level coding [7], multiple antenna techniques [8], different cooperative communication schemes [9,10], and efficient subcarrier allocation methods [11]. The basic functionality of AeroMACS is the support of surface airport communications with vehicle speeds up to 92 km/h (50 kn).…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of a multicarrier technology provides the system with high spectral efficiency, increased robustness against multipath distortions, and a remarkable flexibility in assigning system resources. It was recently shown that further physical layer (PHY) advancements can be achieved by introducing packet level coding [7], multiple antenna techniques [8], different cooperative communication schemes [9,10], and efficient subcarrier allocation methods [11]. The basic functionality of AeroMACS is the support of surface airport communications with vehicle speeds up to 92 km/h (50 kn).…”
Section: Introductionmentioning
confidence: 99%